Penjatuhan Sanksi Terhadap Bani Quraizah: Analisis Gaya Manajemen Konflik Nabi Muhammad Perspektif Thomas-Khilmann - Mawehda, Mawehda (STID Al-Hadid, 2025)
IMPOSING SANCTIONS AGAINST BANI QURAIZAH: AN ANALYSIS OF THE PROPHET MUHAMMAD'S CONFLICT MANAGEMENT STYLE FROM THE PERSPECTIVE OF THOMAS-KHILMANN. The history of the prophethood not only records theological teachings, but also the leadership practices, political decision-making, and management of social conflicts of the Prophet Muhammad saw in certain historical contexts. A critical and contextual understanding of history is important so that Islamic preaching is not reduced to an ahistorical doctrine detached from social reality. One of the most frequently debated historical episodes is the imposition of sanctions on Bani Quraizah after the Battle of the Trench, which is often represented as an act of violence in contemporary discourse. Previous studies tend to be descriptive-historical, historical-critical, or normative-apologetic, not many have analyzed this event through the framework of modern conflict management theory. This study aims to reinterpret this event using the Thomas-Khilmann Conflict Management Style approach. The research was conducted using qualitative methods, analysis was carried out using classical sources such as Sirah Ibn Ishaq, Tarikd al-Tabari, and modern historical literature. The results of this study indicate that the imposition of sanctions on the Bani Quraizah was not a single repressive measure, but rather part of a gradual conflict management process that tended to be collaborative and compromising through agreements and arbitration mechanisms. The novelty of this research lies in the integration of modern conflict management theory into Islamic studies to strengthen the contextual, rational, and civilized narrative of da'wah (Islamic preaching).